Are We There Yet? Progress in Depicting Diverse Images of Beauty in Instagram’s Body Positivity Movement - Lazuka, Rebecca F.; Wick, Madeline R.; Keel, Pamela K.; Harriger, Jennifer A. (Body image, 2020)
•Body positivity posts on Instagram included diverse body sizes and appearances.•Only 43% of posts depicted larger bodies which is not representative of the general population.•A proportion of the posts did contain contradictory messages.•A small proportion of the posts contained messages praising thinness or encouraging weight loss. As the literature on the narrowly defined standards of beauty portrayed in social media has increased, a newer focus on body positivity messages has also emerged. Body positivity challenges the unrealistic standards of beauty present in the media by the promotion and acceptance of diverse body sizes and appearances. In an effort to further understand the messages of body positivity in social media, this study examined the content of 246 body positive posts from the broad Instagram community. Results demonstrated an inclusion and appreciation of diverse physical appearances, as well as themes consistent with messages promoting body positivity. In contrast to content on popular body positivity accounts, several of the posts from the broader Instagram community did, however, contain contradictory messages, such as the promotion of weight loss or the praise of extreme thinness. Future research examining such contradictory messages in body positivity posts and their effects on body image and other related domains is warranted.